HAMBATAN LSM KUNTI BHAKTI DALAM MENINGKATKAN KETERWAKILAN PEREMPUAN DI JABATAN LEGISLATIF KABUPATEN TABANAN TAHUN 2014 - Purnama Sari, Ni Putu Lisa; Erawan, I Ketut Putra; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2018)
ABSTRACT In 2014, Kunti Bhakti LSM contributed a role to improve women's representation in the legislative position. However, the level of representation of women in the legislature of Tabanan Regency in Legislative Elections in 2014 did not reach 30%. The purpose of this thesis is to know how the obstacles of Kunti Bhakti LSM in improving women representation in the legislative position of Tabanan Regency in 2014. The theories that used in this research are liberal Feminist theory and Postfeminist theory. The researcher used qualitative method. Based on the result of the reseach, there is non-governmental organization in the legislative election of 2014 that contributed a role to improve women's representation in the legislative position of Tabanan Regency, namely Kunti Bhakti LSM. The efforts that have been made by Kunti Bhakti LSM is to have become a KPU relation and provided the capacity building for women legislative candidates. However, these efforts were experiencing some obstacles, the first is the internal factors derived from the Kunti Bhakti LSM that is still difficult to awaken women to take a part of the political. The second comes from external factors in which the obstacles of political parties where political parties tend to nominate men than women, because there is still a patriarchal culture in Tabanan regency, the cost candidates, the lack of women's understanding of politics, the potential women and the difficulty in getting permission from the family. Keywords : LSM, Legislative , Women Representation